Taking the Long View: How Well Do Patient Activation Scores Predict Outcomes Four Years Later?. (June 2015) - Hibbard, Judith H.; Greene, Jessica; Shi, Yunfeng; Mittler, Jessica; Scanlon, Dennis
Patient activation is an important predictor of health outcomes and health care usage, yet we do not know how enduring the benefits of greater patient activation are. This study uses a large panel survey of people with chronic conditions ( n = 4, 865) to examine whether a baseline patient activation measure predicts outcomes 4 years later, and whether changes in patient activation measure scores are associated with changes in outcomes. The findings indicate that the benefits of health activation are enduring, yielding benefits in the form of better self-management, improved functioning, and lower use of costly health care services over time. Furthermore, the findings indicate that when activation levels change, many outcomes change in the same direction. Patient activation seems to be an important and modifiable factor for influencing chronic disease outcomes; health care delivery systems can use this information to personalize and improve care.